2014
DOI: 10.1016/j.spen.2014.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Building a Pediatric Neurocritical Care Program: A Multidisciplinary Approach to Clinical Practice and Education from the Intensive Care Unit to the Outpatient Clinic

Abstract: We describe our 10-year experience developing the Ruth D. & Ken M. Davee Pediatric Neurocritical Care Program at Northwestern University Feinberg School of Medicine. The neurocritical care team includes intensivists, neurologists, and an advanced practice nurse who have expertise in critical care neurology and who continue care in long-term follow-up of intensive care unit patients in a dedicated neurocritical care outpatient clinic. Brain-directed critical care requires collaboration between intensivists and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 28 publications
1
19
0
1
Order By: Relevance
“…In our study, we found in line with the literature that neurological system diseases were the most common disease group in which tracheostomy was performed (7). This is because these children are in the higher risk group in terms of mechanical ventilator duration, ventilator-related pneumonia incidence and mortality rates than other children in intensive care unit (8)(9)(10). In 93% of our patients, the reason for admission to our service was respiratory distress.…”
Section: Discussionsupporting
confidence: 85%
“…In our study, we found in line with the literature that neurological system diseases were the most common disease group in which tracheostomy was performed (7). This is because these children are in the higher risk group in terms of mechanical ventilator duration, ventilator-related pneumonia incidence and mortality rates than other children in intensive care unit (8)(9)(10). In 93% of our patients, the reason for admission to our service was respiratory distress.…”
Section: Discussionsupporting
confidence: 85%
“…32 Data are needed to elucidate the optimal configuration and integration of neurocritical care services that affect outcomes. 29,30,33,34 Few centers reported having ICU follow-up clinics, an innovative multidisciplinary effort to address recovery from critical illness. 35 …”
Section: Discussionmentioning
confidence: 99%
“…Advantages of inter-disciplinary cooperation among multi-professional teams have been well documented in several pediatric, medical and surgical conditions, including reduced length of hospital admission and improved quality of life [31][32][33]. Multidisciplinary regular early intervention among Down syndrome children have been shown to signi icantly improve rates of school attendance compared to others not receiving regular early interventions [34].…”
Section: Discussionmentioning
confidence: 99%
“…Neurodevelopment ASD Diagnosis and management [42,38,37] Learning and behavioural problems [43] Language-impairment [44] Cerebral Palsy [45,46] Developmental Surveillance [47] Respiratory Asthma [48] infants with chronic lung disease [49] Neurology Spinal Muscular Atropy (SMA) [50] Traumatic brain injury [51] Epilepsy [52] Neurocritical care [32] Nutritional Obesity [53,54] Health Services Transitioning [55] Minimizing drug errors [55] Genetic Beckwith-Wiedeman syndrome [57] Haemophilia [58] Mental Health Eating disorders in children and adolescents.…”
Section: Specifi C Conditions Literaturementioning
confidence: 99%